30.2: Invited Paper: A RGB chip Full Color Active Matrix Micro‐LEDs Transparent Display with IGZO TFT Backplane. (4th October 2019) - Fan, Jack; Lee, Chia-Yu; Chen, Shu-jhih; Gang, Liu Ming; Jun, Zhang Li; Yang, Sun; Cai, Lu Ma; Fei, Xie Hua; Nian, Liu
Abstract : In this paper, the first time reported the full color active matrix micro‐LEDs (AMLEDs) display with high transparent over 40% which is based on top gate IGZO TFT (Thin film transistor) backplane. This AMLEDs display was successfully developed with flip chip RGB micro‐LEDs that can achieve more than 108% NTSC gamut, while the display is also brighter than 400nits.